A lithium battery cell and a lithium battery
Patent Information
- Application Number
- CN202611213575.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-09-22
AI Technical Summary
[0005]有鉴于此,本发明提供一种锂电池电芯和锂电池,通过在电芯构建“隔离层-吸热层”协同防护体系,解决了现有技术无法在针刺机械滥用场景下实现毫秒级物理隔离短路通道的问题
(1)绝对安全性:通过“自膨胀隔离”与“分布式熔断”的毫秒级双重响应,从物理上杜绝了可持续的大电流短路通路,实现了针刺测试100%的通过率。
Smart Images

Figure CN122800863A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and more particularly to a lithium battery cell and a lithium battery. Background Technology
[0002] While the energy density of lithium-ion batteries continues to improve, their safety, especially under conditions of mechanical abuse, remains a key bottleneck restricting their application in high-reliability fields. The nail penetration test is one of the most stringent methods for simulating internal short circuits in batteries. The instantaneous penetration of the steel needle causes large-area melting of the separator, leading to direct contact between the positive and negative electrodes. This triggers a violent local short-circuit current and Joule heating, with an instantaneous temperature rise reaching hundreds of degrees Celsius. This, in turn, triggers a chain of exothermic reactions such as oxygen evolution in the positive electrode material and electrolyte decomposition, ultimately causing the battery cell to catch fire or explode.
[0003] To improve the safety of needle puncture, existing technologies mainly focus on the following aspects: (1) Material modification: such as using high melting point separators (ceramic coated separators), high stability electrolytes (adding flame retardants), and oxidation-resistant cathode materials. However, these methods often come at the cost of sacrificing the energy density, rate performance, or cost of the battery, and cannot fundamentally block the vicious cycle of "thermal-electric" at the needle puncture point. (2) System-level protection: such as strengthening the battery pack structure, setting pressure relief valves, and adding heat insulation materials. These measures are "secondary protection," which attempt to mitigate the consequences after thermal runaway has occurred in the battery cell, but do not address the root cause of the problem within the battery cell. (3) Local structural design: such as setting a fusible structure at the tab and using low melting point coated electrodes. These designs have a certain effect on local small-scale short circuits, but for large-area, instantaneous, low-resistance direct short circuits caused by needle puncture, their response speed and blocking ability are insufficient, and the needle puncture pass rate cannot stably reach 100%, especially for high energy density battery cells.
[0004] The existing technology has the following drawbacks: (1) It cannot physically isolate the direct contact between the positive and negative electrodes caused by the needle puncture point within a millisecond time. (2) It cannot effectively dissipate or block the huge concentrated heat flow generated by the needle puncture point to prevent it from spreading to the surrounding area. (3) It lacks buffering for the instantaneous mechanical stress of the needle puncture, resulting in the short circuit area being artificially enlarged. (4) Most existing solutions are "passive responses" and lack the design of an "active blocking" mechanism. Summary of the Invention
[0005] In view of this, the present invention provides a lithium battery cell and a lithium battery, which solves the problem that the prior art cannot achieve millisecond-level physical isolation of short-circuit channels in the case of acupuncture and mechanical abuse by constructing a collaborative protection system of "isolation layer-heat absorption layer" in the cell.
[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a lithium battery cell, comprising a positive electrode and a negative electrode, wherein an insulating layer is disposed between the positive electrode and the negative electrode. The isolation layer comprises polymer microspheres and ceramic particles; The isolation layer comprises 30% to 50% polymer microspheres, 40% to 60% ceramic particles, 5% to 10% binder, and 2% to 5% conductive carbon black, based on a total mass percentage of 100%.
[0007] This invention introduces a composite functional layer composed of polymer microspheres and insulating ceramic particles between the positive and negative electrodes. This layer remains insulating and ion-conducting at room temperature (without microsphere expansion). When the temperature at the needle penetration point rises sharply above its trigger temperature (e.g., 120°C), the polymer microspheres expand instantaneously, increasing in volume by 3-5 times. This "squeezes in" the insulating ceramic particles and physically fills the direct contact channels between the positive and negative electrodes formed by the melting of the separator. Within milliseconds, this forces the low-resistance electronic pathway to a high-resistance ionic pathway, fundamentally preventing the generation of large short-circuit currents. The polymer microspheres and ceramic particles in this invention respectively undertake synergistic and complementary functions of "thermally driven stress buffering" and "insulation filling and framework support" within the insulating layer, with a strict "dosage-function" dependency between them. Too little polymer microspheres results in insufficient driving force and delayed response; too much leads to structural collapse and insufficient plug density. Too little ceramic particles result in a lack of rigid framework and insufficient insulation filling; too much leads to loss of toughness and brittle cracking. Only by limiting the mass ratio of the two components to the range specified in this invention can a dense, complete, and resilient insulating plug be formed within a millisecond-level time window, thereby physically sealing the short-circuit channel and ensuring the needle penetration test is passed.
[0008] Based on the above technical solutions, the polymer microspheres further include polyolefins, and the ceramic particles include Al2O3 or SiO2.
[0009] In this invention, the polymer microspheres are preferably made of polyolefin material, based on their ultrafast response to needle-puncture temperature rise, inert compatibility with electrochemical systems, buffering and absorption of mechanical stress, and mature process adaptability. This selection ensures that the isolation layer has completely different physicochemical states at room temperature and high temperature, thereby achieving ion conduction under normal conditions and electron blocking under abnormal conditions. This is the core technical path to achieve an "active isolation" thermal runaway prevention mechanism from the material's origin.
[0010] Based on the above technical solutions, the polyolefin further includes at least one of polyethylene, polypropylene, and ethylene-vinyl acetate copolymer.
[0011] Based on the above technical solutions, the thickness of the isolation layer is further 1~30μm.
[0012] Based on the above technical solution, the base membrane is further described as a porous polymer base membrane, and the raw material of the porous polymer base membrane includes at least one of polyethylene and polypropylene.
[0013] Based on the above technical solution, the outer layer of the battery cell is further covered with a heat-absorbing layer, which includes phase change material microcapsules and graphene sheets; the graphene sheets are arranged along the winding direction parallel to the battery cell.
[0014] On the outermost layer (closest to the shell side) of the battery cell core or stack, a "thermal buffer-dissipation layer" is formed by a directional composite of phase change material (PCM) and highly thermally conductive graphene sheets. The PCM (such as paraffin wax) is used to absorb a large amount of heat and slow down the temperature rise; the graphene sheets are oriented parallel to the direction of the battery cell core, forming a rapid horizontal heat diffusion channel, which quickly conducts and disperses the concentrated heat at the needle point laterally to the entire surface of the battery cell, avoiding the vertical accumulation of heat that could trigger a chain reaction.
[0015] Based on the above technical solutions, the core material of the phase change material microcapsule further includes a phase change material, and the shell material is polymethyl methacrylate.
[0016] Based on the above technical solutions, the mass ratio of the core material to the shell material is further specified as 1:2 to 1:5.
[0017] Based on the above technical solutions, the thickness of the heat-absorbing layer is further 0.1~0.3mm.
[0018] Based on the above technical solutions, the phase change temperature of the phase change material is further specified to be 70~90°C.
[0019] Based on the above technical solutions, the particle size of the phase change material microcapsules is further specified as 5~20μm.
[0020] Based on the above technical solution, the graphene sheet diameter is further specified to be 10~50μm.
[0021] Based on the above technical solutions, further, taking the sum of the mass percentages of the heat-absorbing layers as 100%, it includes 60%~70% phase change material microcapsules, 20%~30% graphene sheets, and 5%~10% binder.
[0022] Based on the above technical solutions, the adhesive further comprises styrene-butadiene-styrene block copolymer (SBS).
[0023] Based on the above technical solutions, the thickness of the heat-absorbing layer is further specified to be 0.1~0.3mm.
[0024] Secondly, the present invention also provides a method for preparing the isolation layer, comprising: dispersing polymer microspheres, ceramic particles, binder and conductive carbon black in a solvent to obtain a slurry, coating the slurry on a base film, and drying it to obtain the isolation layer.
[0025] Thirdly, the present invention also provides a lithium battery, including a lithium battery cell.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) Absolute safety: Through the millisecond-level dual response of "self-expansion isolation" and "distributed circuit breaking", the sustainable high current short circuit path is physically eliminated, achieving a 100% pass rate in the needle penetration test.
[0027] (2) Minimal impact on performance: The amount of functional layer added is precise and the ionic conductivity has been optimized, so it has minimal impact on battery internal resistance, capacity and cycle life (tested to have a capacity retention rate of >90% after 500 cycles).
[0028] (3) Active protection mechanism: It changes the traditional thinking of "blocking" and "leaking" to "active isolation and dissipation", which is an advanced protection concept.
[0029] (4) Good process compatibility: The coating, lamination and other processes involved are all mature processes that are easy to implement on existing production lines. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the acupuncture test in Embodiment 1 of the present invention. Detailed Implementation
[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0032] In the following specific embodiments, the particle size of the polyolefin microspheres is 5~15μm, the particle size of Al2O3 and SiO2 is 0.5~3μm, and the sheet size of graphene is 10~50μm.
[0033] Unless otherwise specified, all materials used are standard materials and are available commercially.
[0034] The molecular weights of polyethylene, polypropylene, and ethylene-vinyl acetate copolymers range from 300,000 to 900,000.
[0035] Example 1 This embodiment provides a lithium battery cell, the preparation method of which includes the following steps: I. Preparation of the positive electrode sheet Using NCM622 ternary material as the positive electrode active material, the positive electrode slurry was prepared according to the conventional lithium-ion battery electrode preparation process. The positive electrode slurry was coated on the current collector, and the positive electrode sheet was obtained after drying, rolling and cutting. The designed capacity is 5Ah.
[0036] II. Preparation and Composite of the Isolation Layer (1) Based on the sum of weight percentages of 100%, polyethylene microspheres account for 40%, Al2O3 accounts for 50%, polyvinylidene fluoride (PVDF) accounts for 7%, and conductive carbon black accounts for 3%. Weigh 40g of polyethylene microspheres, Al2O3, PVDF and conductive carbon black according to the above weight percentages, disperse the above components in N-methylpyrrolidone solvent, stir at high speed and mix evenly to prepare a composite slurry with a solid content of 30%.
[0037] (2) A PE porous base membrane with a thickness of 9 μm was selected as the support layer. The above-mentioned composite slurry was coated on both sides of the PE base membrane using a microgravure coating method. The dry weight coating amount on one side was 10 g / m². After coating, the membrane was dried in an oven and then wound up to obtain a composite separator with an isolation layer. The porosity of the isolation layer at room temperature was 40%, and the ionic conductivity met the requirements for normal battery operation.
[0038] III. Preparation of the heat-absorbing layer (1) Preparation of phase change material microcapsules: Using 10g of paraffin as the core material, 10g of paraffin, 20g of methyl methacrylate monomer, 0.6g of styrene-maleic anhydride copolymer, and 0.3g of benzoyl peroxide were added to 100mL of deionized water and emulsified at high speed to form an oil-in-water emulsion. The temperature was raised to 75°C and the reaction was carried out under stirring for 5 hours, so that methyl methacrylate underwent interfacial polymerization on the surface of the paraffin droplets to form a polymethyl methacrylate shell. After the reaction was completed, the microcapsules of phase change material were obtained by cooling, filtering, washing, and drying.
[0039] Based on the total mass percentage of the heat-absorbing layer being 100%, the phase change material microcapsules account for 65%, the graphene sheets account for 30%, and the styrene-butadiene-styrene block copolymer (SBS) accounts for 5%.
[0040] (2) Weigh 65g of phase change material microcapsules, graphene sheets and SBS according to the above mass percentages. After uniformly mixing the above components, use casting extrusion molding and stretching orientation process to orient the graphene sheets along the film plane to make a composite film with a thickness of 0.2mm, i.e. heat absorption layer.
[0041] IV. Assembly of Battery Cells (1) The positive electrode sheet, the composite separator with the isolation layer and the negative electrode sheet prepared above are stacked in the order of "positive electrode sheet / composite separator / negative electrode sheet" to form a core.
[0042] (2) The heat-absorbing layer obtained in step four is tightly wrapped around the outermost ring of the core.
[0043] (3) The core with heat dissipation layer is loaded into the soft pack shell, conventional lithium-ion battery electrolyte is injected, and after encapsulation, formation and capacity testing, the 5Ah NCM622 / graphite system soft pack battery cell of the present invention is obtained.
[0044] Example 2 This embodiment provides a lithium battery cell, the preparation method of which includes the following steps: I. Preparation of the positive electrode sheet Using NCM622 ternary material as the positive electrode active material, the positive electrode slurry was prepared according to the conventional lithium-ion battery electrode preparation process. The positive electrode slurry was coated on the current collector, and the positive electrode sheet was obtained after drying, rolling and cutting. The designed capacity is 5Ah.
[0045] II. Preparation and Composite of the Isolation Layer (1) Based on the sum of weight percentages of 100%, polypropylene microspheres account for 30%, SiO2 accounts for 60%, PVDF accounts for 5%, and conductive carbon black accounts for 5%. Weigh 30g of polypropylene microspheres, Al2O3, PVDF and conductive carbon black according to the above weight percentages, disperse the above components in N-methylpyrrolidone solvent, stir at high speed and mix evenly to prepare a composite slurry with a solid content of 30%.
[0046] (2) A PE porous base membrane with a thickness of 9 μm was selected as the support layer. The above-mentioned composite slurry was coated on both sides of the PE base membrane using a microgravure coating method. The dry weight coating amount on one side was 10 g / m². After coating, the membrane was dried in an oven and then wound up to obtain a composite separator with an isolation layer. The porosity of the isolation layer at room temperature was 50%, and the ionic conductivity met the requirements for normal battery operation.
[0047] III. Preparation of the heat-absorbing layer (1) Preparation of phase change material microcapsules: Using paraffin as the core material, 10g of paraffin, 30g of methyl methacrylate monomer, 0.6g of styrene-maleic anhydride copolymer, and 0.3g of benzoyl peroxide were added to 100mL of deionized water and emulsified at high speed to form an oil-in-water emulsion. The temperature was raised to 70°C and reacted for 4 hours under stirring to allow methyl methacrylate to undergo interfacial polymerization on the surface of the paraffin droplets, forming a polymethyl methacrylate shell. After the reaction, the microcapsules were obtained by cooling, filtering, washing, and drying. Based on the total mass percentage of the endothermic layers as 100%, the microcapsules accounted for 70%, the graphene sheets accounted for 20%, and the SBS accounted for 10%.
[0048] (2) Weigh 70g of phase change material microcapsules, graphene sheets and SBS according to the above mass percentages. After uniformly mixing the above components, use casting extrusion molding and stretching orientation process to orient the graphene sheets along the film plane to make a composite film with a thickness of 0.2mm, i.e. heat absorption layer.
[0049] IV. Assembly of Battery Cells (1) The positive electrode sheet, the composite separator with the isolation layer and the negative electrode sheet prepared above are stacked in the order of "positive electrode sheet / composite separator / negative electrode sheet" to form a core.
[0050] (2) The heat-absorbing layer obtained in step four is tightly wrapped around the outermost ring of the core.
[0051] (3) The core with heat dissipation layer is loaded into the soft pack shell, conventional lithium-ion battery electrolyte is injected, and after encapsulation, formation and capacity testing, the 5Ah NCM622 / graphite system soft pack battery cell of the present invention is obtained.
[0052] Example 3 This embodiment provides a lithium battery cell, the preparation method of which includes the following steps: I. Preparation of the positive electrode sheet Using NCM622 ternary material as the positive electrode active material, the positive electrode slurry was prepared according to the conventional lithium-ion battery electrode preparation process. The positive electrode slurry was coated on the current collector, and the positive electrode sheet was obtained after drying, rolling and cutting. The designed capacity is 5Ah.
[0053] II. Preparation and Composite of the Isolation Layer (1) Based on the sum of weight percentages of 100%, ethylene-vinyl acetate copolymer microspheres account for 50%, Al2O3 accounts for 40%, PVDF accounts for 4%, and conductive carbon black accounts for 6%. Weigh 50g of ethylene-vinyl acetate copolymer microspheres, Al2O3, PVDF and conductive carbon black according to the above weight percentages, disperse the above components in N-methylpyrrolidone solvent, stir at high speed and mix evenly to prepare a composite slurry with a solid content of 30%.
[0054] (2) A PE porous base membrane with a thickness of 9 μm was selected as the support layer. The above-mentioned composite slurry was coated on both sides of the PE base membrane using a microgravure coating method. The dry weight coating amount on one side was 10 g / m². After coating, the membrane was dried in an oven and then wound up to obtain a composite separator with an isolation layer. The porosity of the isolation layer at room temperature was 35%, and the ionic conductivity met the requirements for normal battery operation.
[0055] III. Preparation of the heat-absorbing layer (1) Preparation of phase change material microcapsules: Using paraffin as the core material, 10g of paraffin, 50g of methyl methacrylate monomer, 0.6g of styrene-maleic anhydride copolymer, and 0.3g of benzoyl peroxide were added to 100mL of deionized water and emulsified at high speed to form an oil-in-water emulsion. The temperature was raised to 80°C and reacted for 6 hours under stirring to allow methyl methacrylate to undergo interfacial polymerization on the surface of the paraffin droplets, forming a polymethyl methacrylate shell. After the reaction, the microcapsules were obtained by cooling, filtering, washing, and drying. Based on the total mass percentage of the endothermic layers as 100%, the microcapsules accounted for 65%, the graphene sheets accounted for 28%, and the SBS accounted for 7%.
[0056] (2) Weigh 65g of phase change material microcapsules, graphene sheets and SBS according to the above mass percentages. After uniformly mixing the above components, use casting extrusion molding and stretching orientation process to orient the graphene sheets along the film plane to make a composite film with a thickness of 0.2mm, i.e. heat absorption layer.
[0057] IV. Assembly of Battery Cells (1) The positive electrode sheet, the composite separator with the isolation layer and the negative electrode sheet prepared above are stacked in the order of "positive electrode sheet / composite separator / negative electrode sheet" to form a core.
[0058] (2) The heat-absorbing layer obtained in step four is tightly wrapped around the outermost ring of the core.
[0059] (3) The core with heat dissipation layer is loaded into the soft pack shell, conventional lithium-ion battery electrolyte is injected, and after encapsulation, formation and capacity testing, the 5Ah NCM622 / graphite system soft pack battery cell of the present invention is obtained.
[0060] Application examples The battery cell prepared in Example 1 was subjected to performance testing.
[0061] Under normal temperature (25°C±2°C) conditions, a 500-cycle test was conducted with a 1C / 1C charge / discharge current and a charge / discharge voltage range of 3.0V~4.2V. The test results are as follows: initial discharge capacity: 5.02Ah; capacity retention after 500 cycles: 94.2%; internal resistance growth rate after 500 cycles: 4.1%.
[0062] Comparative Example 1 The difference between this comparative example and Example 1 is that step two of this comparative example does not contain an isolation layer, but only a 9μm PE porous base film.
[0063] Comparative Example 2 The difference between this comparative example and Example 1 is that the amount of polyethylene microspheres used in this comparative example is too high, accounting for 70%, and Al2O3 accounts for 20%.
[0064] Comparative Example 3 The difference between this comparative example and Example 1 is that the amount of polyethylene microspheres used in this comparative example is too small, accounting for 20%, and Al2O3 accounts for 70%.
[0065] Comparative Example 4 The difference between this comparative example and Example 1 is that step two of this comparative example does not contain Al2O3.
[0066] Performance testing 1. The needle penetration test was performed on the battery cells prepared in Example 1 and Comparative Examples 1-4 according to the needle penetration test method in the national standard GB / T 31485-2015. The test method included: using a high-temperature resistant steel needle with a diameter of φ5mm, vertically piercing the central part of the battery cell at a speed of 25mm / s, and keeping the steel needle in the battery cell.
[0067] The test results are shown in Table 1.
[0068] Table 1 Results of acupuncture test
[0069] As shown in Table 1, in Embodiment 1 of the present invention, at the moment the steel needle pierces the cell, the cell voltage drops from its full charge voltage to approximately 2.5V and then remains stable without further decline. The highest surface temperature of the cell rises rapidly and then stabilizes at approximately 85°C (corresponding to the phase change plateau temperature of the phase change material), subsequently decreasing slowly as heat dissipates. Throughout the entire test, the cell exhibits no smoke, no fire, and no explosion. After the steel needle is left stationary for 1 hour, the cell voltage does not rebound, and the outer casing does not bulge or deform. The needle penetration pass rate is 100% (all three parallel tests passed).
[0070] Disassembly and analysis of the Example 1 battery cell after the needle penetration test revealed the following: Figure 1As shown, (1) inside and around the needle-punched channel, the thermoplastic microspheres in the original isolation layer have fully expanded, tightly filling the insulating ceramic particles into the direct contact channel between the positive and negative electrodes caused by the needle-punching, forming a white and dense insulating plug; (2) in the outer heat-absorbing layer, the phase change material microcapsules have completely melted into the liquid phase (indicating that they have fully absorbed the latent heat of phase change), and the graphene sheet orientation structure remains intact without damage.
[0071] Comparative Example 1: The moment the steel needle pierced the cell, the cell voltage plummeted to 0V, and the maximum temperature surged to over 400°C. The cell then emitted a large amount of white smoke, followed by a violent fire. The needle penetration pass rate was 33.33% (2 EAs of fire and 1 EA of smoke in 3 parallel tests). This is because the needle penetration caused the PE separator to be punctured, creating a low-resistance short-circuit path through direct contact between the positive and negative electrodes. Due to the limited rupture temperature of the PE separator, the localized high temperature generated at the moment of needle penetration caused the separator to melt rapidly, further expanding the short-circuit area between the positive and negative electrodes. The enormous short-circuit current instantly generated a large amount of Joule heat, triggering a chain of exothermic reactions such as oxygen evolution in the positive electrode material and electrolyte decomposition, ultimately leading to the cell fire.
[0072] Comparative Example 2: After the steel needle was inserted, the cell voltage dropped to approximately 1.8V and then slowly continued to decrease. The highest surface temperature of the cell rose to approximately 180°C, and the cell emitted smoke but did not ignite or explode. The needle penetration pass rate was 66.6% (smoke occurred twice and fire occurred once in three parallel tests). This was because the excessively high content of polyolefin microspheres (70%) resulted in excessively low porosity of the insulating layer at room temperature (the measured porosity was only about 25%), significantly increasing the battery's internal resistance. Upon needle penetration, the excessive microspheres expanded simultaneously, generating excessive compressive force, which cracked the coating structure and damaged its integrity. Simultaneously, the excessively expanded microspheres occupied the filling space of the ceramic particles, weakening the compactness of the insulating plug and preventing the short-circuit path from being effectively sealed. Therefore, although some short-circuit current was suppressed and did not trigger a violent fire or explosion, a continuous leakage current still existed (voltage slowly decreased).
[0073] Comparative Example 3: Upon needle insertion, the cell voltage plummeted to 0.5V, and the cell surface temperature rapidly rose to approximately 350°C, causing the cell to ignite. The needle penetration pass rate was 33.3% (1 instance of smoke and 2 instances of fire in 3 parallel tests). This is because when the polyethylene microsphere content was insufficient (20%), the heat generated by needle penetration was insufficient to drive a sufficient number of microspheres to expand sufficiently and push the ceramic particles into the short-circuit channel. Simultaneously, an excessively high ceramic particle content (70%) resulted in excessive rigidity and increased brittleness of the coating at room temperature, making it prone to overall fragmentation rather than controlled deformation during needle penetration. The insulating layer could not form an effective insulating plug within milliseconds, the short-circuit current was not effectively blocked, and a large amount of Joule heat was continuously generated inside the cell, ultimately leading to thermal runaway and fire. This result indicates that when the microsphere content is below the 30% lower limit specified in this invention, it cannot provide sufficient "driving force" to complete physical filling.
[0074] Comparative Example 4: Upon the moment the steel needle pierced the cell, the cell voltage plummeted to 0V, and the highest surface temperature of the cell surged to over 400°C. The cell then emitted a large amount of white smoke, followed by a violent fire. The needle penetration pass rate was 33.33% (2 EA of fire and 1 EA of smoke in 3 parallel tests). This is because, in the absence of Al2O3 ceramic particles, although the polyethylene microspheres expand upon heating, the expanded microspheres only form a soft polymer plug. The core role of ceramic particles in this invention is to act as a "filler," pushed into the short-circuit channel by the mechanical force generated by the expansion of the microspheres, forming a rigid, dense insulating plug. Without ceramic particles, the expansion of the polymer microspheres alone cannot effectively block the short-circuit channel between the positive and negative electrodes. Polymers are prone to deformation and flow at high temperatures, failing to form a durable physical barrier. Therefore, the short-circuit current is not sufficiently suppressed, leading to continuous heat generation inside the cell and ultimately thermal runaway. The results indicate that ceramic particles are an indispensable rigid skeleton component for forming an effective insulating plug, and when their content is below the 40% lower limit specified in this invention, the insulating layer loses its plugging function.
[0075] In summary, this invention provides a lithium battery cell and a lithium battery. By constructing a collaborative protection system of "isolation layer-heat absorption layer" in the cell, it solves the problems of existing technologies being unable to achieve millisecond-level physical isolation of short-circuit channels under abusive conditions such as needle penetration, ineffective dissipation of concentrated heat flow, and lack of mechanical stress buffering mechanism leading to an expansion of the short-circuit area.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A lithium battery cell, comprising a positive electrode and a negative electrode, characterized in that, An insulating layer is provided between the positive electrode and the negative electrode. The isolation layer comprises polymer microspheres and ceramic particles; The isolation layer comprises 30% to 50% polymer microspheres, 40% to 60% ceramic particles, 5% to 10% binder, and 2% to 5% conductive carbon black, based on the total mass percentage of the isolation layer as 100%.
2. The lithium battery cell as described in claim 1, characterized in that, The polymer microspheres comprise polyolefins, and the ceramic particles comprise Al2O3 or SiO2.
3. The lithium battery cell as described in claim 2, characterized in that, The polyolefin includes at least one of polyethylene, polypropylene, and ethylene-vinyl acetate copolymer.
4. The lithium battery cell as described in claim 1, characterized in that, The thickness of the isolation layer is 1~30μm.
5. The lithium battery cell as described in claim 1, characterized in that, The outer layer of the battery cell is covered with a heat-absorbing layer, which includes phase change material microcapsules and graphene sheets; The graphene sheets are arranged along a winding direction parallel to the battery cell.
6. The lithium battery cell as described in claim 5, characterized in that, The core material of the phase change material microcapsule includes a phase change material, and the shell material includes polymethyl methacrylate.
7. The lithium battery cell as described in claim 5, characterized in that, Based on the total mass percentage of the heat-absorbing layers being 100%, the components include 60%~70% phase change material microcapsules, 20%~30% graphene sheets, and 5%~10% binders.
8. The lithium battery cell as described in claim 5, characterized in that, The thickness of the heat-absorbing layer is 0.1~0.3mm.
9. A method for preparing an isolation layer, characterized in that, The process includes the following steps: dispersing the polymer microspheres, ceramic particles, binder and conductive carbon black as described in any one of claims 1 to 8 in a solvent to obtain a slurry; coating the slurry onto a base film; and drying to obtain the isolation layer.
10. A lithium battery, characterized in that, Including the lithium battery cell as described in any one of claims 1 to 8.